Effect of Cu interlayer on the microstructure and strength for brazing of Tungsten/316L steel - Wang, Meng (2020)
Brazing is an effective technique for joining tungsten and steel. However, the high residual stresses are produced due to the different coefficients of thermal expansions between tungsten and steel. Compared with the direct brazing with BNi-2 foil filler, BNi-2/Cu/ BNi-2 multiple interlayer was used as filler to minimize the residual stresses between tungsten and 316L steel. The brazing experiments were conducted at 1050 °C for 25 min using Cu foils with different thickness. The results show that tungsten and 316L steel have been successfully joined by brazing. The intermetallic compound of NiW formed at the W/BNi-2 interface, which was detrimental to the strength of the joint. The microhardness of different diffusion zones is higher than that of the substrates owing to the formation of intermetallic compound and solid solution. All specimens of shear testing fractured at the W/BNi-2 interface close to W substrate, and the average strength of joints was 197, 275 and 268 MPa with multiple interlayer thickness of 0.2 , 0.1 and 0.05 mm copper foil, respectively, while the average strength of joints was 143 MPa with BNi-2 foil filler. The significant increase in the joint shear strength can be ascribed to the Cu foil in the multiple interlayer because of with excellent plasticity and toughness.